A 3D printing approach to microfluidic devices for enhanced oil recovery research: An updated perspective - Chantal T. Tracey; Egor O. Ryabchenko; Mariia A. Moshkova; Pavel V. Krivoshapkin; Elena F. Krivoshapkina (Petroleum Research)
Reservoir simulation uses numerical models to study how reservoir properties impact oil recovery. However, numerical modelling is insufficient and is often paired with physical simulation, where physical models are used to verify and improve simulation results. Historically, physical simulation was conducted using difficult-to-extract reservoir rock samples; however, microfluidic devices (MFDs) have emerged as viable substitutes. Unfortunately, conventional approaches to MFD fabrication leads to devices with physical and chemical properties dissimilar to that of reservoir rock – which can decrease simulation accuracy. Thanks to significant advancements in three-dimensional printing, it can be used to fabricate MFDs with properties and dimensions close to those of reservoir rocks thanks to high resolution, good dimensional accuracy, and a wide range of printable substrates, resulting in more accurate simulation aimed at maximizing oil recovery.